Ouabain-mediated downregulation of ALKBH5 and IGF2BP2 inhibits the malignant progression of DLBCL - Hong, Yuxin; Ma, Hehua; Yang, Haoyi; Zhu, Yuning; Wei, Yuan; Xu, Zhenzhen; Zhang, Yuwen; Jin, Dandan; Chen, Zhiyou; Song, Wei; Li, Juan (Frontiers in Pharmacology, 2024)
m 6 A modification is a crucial epigenetic regulatory mechanism in diffuse large B-cell lymphoma (DLBCL). Low-dose cardiotonic drugs have been shown to induce apoptosis in DLBCL cells through epigenetic modulation. However, the involvement of the cardiotonic drug ouabain in the malignant progression of DLBCL remains unclear. Our study revealed that ouabain indeed contributes to the malignant progression of DLBCL through m 6 A modification. Through qPCR analysis, we observed a negative correlation between ouabain concentration and the expression levels of the demethylase ALKBH5 and the m 6 A-binding protein IGF2BP2 in DLBCL cells. Furthermore, high expression levels of ALKBH5 and IGF2BP2 were identified in both the GEO database and DLBCL patient tissue samples. Notably, elevated ALKBH5 and IGF2BP2 promoted cell proliferation both in vitro and in vivo. Inhibition of their expression rendered DLBCL cells more sensitive to ouabain treatment, resulting in significant suppression of cell proliferation, G1/S phase cell cycle arrest, and increased apoptosis. In summary, our results clarify that the demethylase ALKBH5 and the m 6 A-binding protein IGF2BP2 are involved in the malignant progression of DLBCL, and that the cardiotonic drug ouabain can inhibit the proliferation of DLBCL cells by inhibiting the expression of ALKBH5 and IGF2BP2, which provides new insights into the targeted treatment of DLBCL.